Human 6-sulfo LacNAc (slan) dendritic cells have molecular and functional features of an important pro-inflammatory cell type in lupus erythematosus - Hänsel, Anja; Bidier, Mona; Lorenz, Hanns-Martin; Döbel, Thomas; Enk, Alexander; Schäkel, Knut (Journal of autoimmunity, 2013)
Lupus erythematosus (LE) is an autoimmune disease with evidence for an IL-23- and IL-17-induced immunopathology. Little is known about the type of dendritic cells supporting this immune response. We recently demonstrated the strong Th1- and Th17-T-cell inducing capacity of human 6-sulfo LacNAcdendritic cells (slanDCs), and identiﬁed slanDCs as inﬂammatory dermal dendritic cells in psoriasis locally expressing IL-23, TNF-a and inducible nitric oxide synthase (iNOS). In this study, we investigated the role of slanDCs in LE. Using immunohistochemistry, we identiﬁed slanDCs at increased frequency in affected skin lesions of cutaneous and systemic LE. slanDCs were found scattered in the dermal compartment and also clustered in lymph follicle-like structures. Here, they colocalized with T cells in the periphery but not with B cells in the center. The positive staining of dermal slanDCs for TNFa indicated their pro-inﬂammatory status. In vitro the production of TNF-a was induced when slanDCs were cultured in the presence of serum from patients with LE. Stimulatory components of LE serum were previously identiﬁed as autoimmune complexes with ssRNA binding to TLR7 and TLR8. We found that slanDCs express mRNA for TLR7 and TLR8. slanDCs stimulated with ssRNA, selective TLR7 or TLR8 ligands responded with high-level TNF-a and IL-12 production. In contrast to slanDCs, the population of CD1cþ DCs and plasmacytoid DCs (pDCs) expressed either TLR7 or TLR8, and their production of TNF-a and IL-12 to respective ligands was far less pronounced. We conclude that slanDCs have molecular and functional features of a pro-inﬂammatory myeloid DC type relevant for the immunopathogenesis of LE.